Analisis Perbandingan Pajak Hotel, Restoran, Reklame, Dan Retribusi Kebersihan Sebelum Dan Sesudah Pandemi Di Provinsi Aceh Periode 2018-2021 - Hidayat, Ferry; Gurusinga, Latersia Br; Filbert, Filbert (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The COVID-19 pandemic in 2020 caused a decreased Revenue of Local Taxes and Retributions in Indonesia. In 2022, there will be a simplification for the types of Local Taxes and Retributions from Law Number 28 of 2009 to Law Number 1 of 2022 because there are too many types of Local Taxes and Retributions, which made monitoring difficult. This study aimed to analyze and compare Hotel Tax, Restaurant Tax, Billboard Tax, and Cleaning Retribution before and after the pandemic in Regencies/Cities of Aceh Province. Data analysis of the study used quantitative descriptive and comparative to compare the increased or decreased revenues between two samples before and after the pandemic. The results of the Wilcoxon Signed-Ranks Test show that there is a significant difference in revenue from Hotel Tax and Billboard Tax before and after the pandemic. Revenue from Hotel Tax experienced a significant decrease, while Revenue from Billboard Tax experienced a significant increase. Meanwhile, there is no significant difference between from Revenue Restaurant Tax and Revenue from Cleaning Retribution before and after the Pandemic.